2001
DOI: 10.1016/s0891-5849(01)00618-9
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-rich extract decreases indices of lipid peroxidation and DNA damage in vitamin E-depleted rats

Abstract: Abstract-Anthocyanins are secondary plant metabolites responsible for the blue, purple, and red color of many plant tissues. The phenolic structure of anthocyanins conveys marked antioxidant activity in model systems via donation of electrons or hydrogen atoms from hydroxyl moieties to free radicals. Dietary intakes of anthocyanins may exceed 200 mg/day, however, little is known about their antioxidant potency in vivo. Consequently, the aim of this study was to establish whether anthocyanins could act as putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(131 citation statements)
references
References 27 publications
4
114
0
10
Order By: Relevance
“…[8][9][10]27) Ramirez-Tortosa et al reported that anthocyanin-rich extract decreases hepatic lipid peroxidation in vitamin E-depleted rats. 30) In this study, increasing TBARS levels in the liver homogenate were found in GalN-intoxicated rats, consistent with previous results. 8,9,27) In contrast, PPE treatment tends to attenuate the increased TBARS value in the liver homogenate.…”
Section: Discussionsupporting
confidence: 93%
“…[8][9][10]27) Ramirez-Tortosa et al reported that anthocyanin-rich extract decreases hepatic lipid peroxidation in vitamin E-depleted rats. 30) In this study, increasing TBARS levels in the liver homogenate were found in GalN-intoxicated rats, consistent with previous results. 8,9,27) In contrast, PPE treatment tends to attenuate the increased TBARS value in the liver homogenate.…”
Section: Discussionsupporting
confidence: 93%
“…These diets contain compounds such as antioxidants [25]. Positive effects of consumption of foods containing antioxidants in improving cardiovascular disease have been reported in clinical researches [17].…”
Section: Discussionmentioning
confidence: 99%
“…According to Serraino et al [43], ATH-rich blackberry juice, containing cyanidin-3-O-glucoside, is a scavenger of peroxynitrite, exerting a protective effect against endothelial dysfunction and vascular failure. Ramirez-Tortosa et al showed that ATH-rich extracts decreased hepatic lipid peroxidation under oxidative stress conditions in rats [44]. The studies on an anthocyanin aglycone, pelargonidin, performed by Tsuda et al [45] showed that this compound protects tyrosine from undergoing nitration via peroxynitrite scavenging.…”
Section: Disscusionmentioning
confidence: 99%